Haemophilus influenzae urethritis and orchiepididymitis: A case report - Mohammad Razban (JEM Reports)
Background: Mainly known as a cause of pulmonary infections or meningitis, Haemophilus influenzae has rarely been described as an etiology of urinary tract infections and even less as a cause of orchitis or epididymitis. Case report: This paper describes a rare case of a patient who presented to our emergency department with urethral discharge, swelling of the right testicle, and fever consistent with a diagnosis of urethritis and orchepididymitis. Initially, we suspected a sexually transmitted disease such as chlamydia or gonorrhea. However, the urethral smear and urine culture revealed the presence of Haemophilus influenzae as the causative agent. A first therapy with Ceftriaxone and Azithromycin followed by doxycycline did not completely resolve symptoms. A new course of antibiotherapy with Ciprofloxacin led to complete remission. Why should an emergency physician be aware of this?: Haemophilus influenzae can occasionally present with urethral discharge and symptoms of orchiepididymitis similar to those of a sexually transmitted disease. It is crucial for physicians to remember that this pathogen also causes genitourinary tract infections, given that most strains are resistant to Azithromycin. Consequently, they should adapt antibiotic therapy and investigations accordingly in these cases.